Re-defining stewardship in the Niger Delta: A graft or ‘giraffe’ principle? - Ahiamadu, A (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
The author grew up in Ogba (Nigeria) where the land and wetlands meant everything for the survival of the various communities of the Niger Delta. There has been in this region an ethic of holistic stewardship which people exercised in all matters of land ownership and use especially within Ogba and Ekpeye before the advent of oil exploration, exploitation and exportation. This ethic has been based on what I have called a “giraffe principle” as opposed to a “graft principle” which is being applied in the sharing of oil wealth by certain stakeholders including both multinational oil companies and various Nigerian governments. By means of “graft” the wealth of major stakeholders like oil bearing communities have been expropriated under the guise of 13% derivation policy and this has aggravated the negative attitude of oil producing communities towards the expropriators, that is both State agencies and multinational oil companies. It has created social and economic tensions wrongly tagged “militancy presently being repressed by government combat forces. This article suggests a solution which calls for the application of a “giraffe principle” prescribing a tripartite ethic of sharing the oil wealth in a humane, prudent and liberating manner.